Faraday’s Iron Ring Experiment 1831’ Explained Better with ‘Gill’s Electronic Theory of Magnetism after 1964 - Gill, Avtar Singh (Innovations in Science and Technology Vol. 8, 2022)
It will be explained why ‘Gill’s electronic theory of magnetism 1964’ and its dot product equations should replace ‘Maxwell’s dipole theory of magnetism 1873’ and its cross-product equations. The following issues related to Maxwell’s equations will be re-visited and explained with the help of ‘Gill’s electronic theory of magnetism 1964’: Faraday’s law of induction [1] will be explained with the help of ‘Gill’s electronic theory of magnetism 1964’ and Faraday’s iron ring experiment of 1831 leads us to the working of a transformer. Ampere’s law and Ampere’s right-hand rule to be combined with ‘Gill’s electronic theory of magnetism 1964’. Magnetic Gauss’ law to be replaced with ‘Gill’s electronic theory of magnetism 1964’. Electric Gauss’ law will be modified. ‘Gill’s electronic theory of magnetism 1964’ shows that the magnetic force has its longitudinal and its positive and negative torque components and how the two opposing forces from the two ends of a magnet entwine to manifest as a single magnetic force B. The electrical force E will be shown to be a combination of the electron (-e) based negative force and the proton (+e) based positive force. How a copper wire in the center of an electric coil can develop an increased electron (-e) based electric current which is also rotating around the central axis of the coil (Coil effect)n will be explained and calculated and should be used as a renewable energy source originating from the SUN. In the end, it will also be shown that the travelling force as a wave is not a combination of the electrical force and the electromagnetic force (or magnetic force), but a combination of the negative electron (-e) dependant force and the positive proton (+e) dependant force as they entwine while heading for each other.